2022
DOI: 10.35784/pe.2022.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Badania nad poprawą wyników małych i mikroprzedsiębiorstw poprzez stosowanie zielonych innowacji

Abstract: It is an important goal of China’s 2025 Strategy to build an environmental governance system with the government as the leading role, enterprises as the main body, and social organizations and the public all participate actively. In this context, whether and how small and micro enterprises, as a force of rejuvenating the country through science and technology, participate in the construction of environmental governance system is discussed in this paper. This study uses the 12th China small and micro enterprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This thesis is confirmed by the results obtained from the analysis of energy efficiency of spring wheat production which demonstrates that conventional tillage contributes to increased production costs (e.g. fuel inputs are about 30% higher than for conservation tillage) [21,[26][27][28][29][30][31][32]. Therefore, conservation tillage combined with cultivation of white mustard as a catch crop can be tentatively recommended to be applied in agricultural practice.…”
Section: Specificationmentioning
confidence: 54%
“…This thesis is confirmed by the results obtained from the analysis of energy efficiency of spring wheat production which demonstrates that conventional tillage contributes to increased production costs (e.g. fuel inputs are about 30% higher than for conservation tillage) [21,[26][27][28][29][30][31][32]. Therefore, conservation tillage combined with cultivation of white mustard as a catch crop can be tentatively recommended to be applied in agricultural practice.…”
Section: Specificationmentioning
confidence: 54%
“…To enhance MSE performance and address perceived environmental volatility, a selection mechanism could choose the optimal SOIPE for incremental improvements. Cao et al (2022) [6] reported that return on assets is a measure of the performance of MSEs.…”
Section: Literaturementioning
confidence: 99%
“…Their role has been to propel regional growth and maintain social stability. Apart from providing jobs, MSEs are responsible for most technological and managerial innovations and contribute to the development of the economy [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other sectors, the mining industry is responding to concerns about the environmental friendliness of these products. For example, Rio Tinto and Alcoa formed a joint venture with Apple to create the world's fi rst zero-emission aluminum production [15].…”
Section: Introductionmentioning
confidence: 99%